Microsoft SQL Server 2000 unleashed - Rankins, Ray (Sams, 2003)
Microsoft SQL Server 2000 Unleashed, 2E offers a variety of topics for system and database administrators to help them learn new features of the product and to solve problems they face on a daily basis. It shows them how to build upon their working knowledge of the product and take their experience and knowledge to a higher level. This new edition of Microsoft SQL Server 2000 Unleashed covers the latest updates and service packs to SQL Server 2000, including full support for XML, notification services, and SQL Server CE.